Study on the effect of surface tannic acid/silane conversion film on properties of epoxy resin coatings. Issue 4 (1st July 2019) - Xing, Tianji; Ying, Lixia; Wu, Chunxi; Fu, Zhen; Wang, Guixiang
Abstract : Purpose: The purpose of this paper is to improve binding force between the coating and the steel substrate by using chemical modification on the steel surface; at the same time, it can also increase the corrosion resistance of the coating. Design/methodology/approach: The main components of the conversion film include tannic acid, sodium molybdate and silane coupling agent KH560. After the preparation was completed, the samples were tested and analyzed, including surface morphology, conversion film components, bonding force with organic resins and corrosion resistance. Finally, it drew a conclusion that the conversion film can greatly improve the bonding strength of the steel substrate and epoxy resin. Findings: When the content of tannic acid is 4 g/L meanwhile the content of KH560 is 20 g/L, the conversion film has the strongest binding force with epoxy resin, from 2.15 Mpa of untreated steel to 4.60 Mpa, growth of 140 per cent. At the same time, the resulting conversion film also improves the corrosion resistance of the steel surface by a small margin. Originality/value: A method of enhancing the bond between an epoxy coating and steel is provided. Verify the mechanism of this method.